2015
DOI: 10.1007/s10072-015-2156-7
|View full text |Cite
|
Sign up to set email alerts
|

Migraine attacks in the pharmacy: a gender subanalysis on treatment preferences

Abstract: In 2014 our group published the results of a survey conducted in Piedmont, Italy, on the patterns of use and dispensing of drugs in patients requesting assistance from pharmacists for relief of a migraine attack. Epidemiological studies on migraine have consistently shown that migraine is far more common among women than men. This gender difference is also reflected in the higher percentage of women visiting a pharmacy to obtain treatment or advice for headache attacks. In this study, we further explored gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“…It is known, however, that migraine and many of the underlying disorders leading to secondary headache production afflict women more than men ( Hu et al, 1999 ; Haast et al, 2012 ). A higher percentage of women migraineurs are also reported to seek medical care, and use triptans, more often than men ( Brusa et al, 2015 ). Additionally, it has been suggested that women are more susceptible to secondary headache production in both traumatic brain injury and ischemic stroke compared to males ( Tentschert et al, 2005 ; Lucas et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known, however, that migraine and many of the underlying disorders leading to secondary headache production afflict women more than men ( Hu et al, 1999 ; Haast et al, 2012 ). A higher percentage of women migraineurs are also reported to seek medical care, and use triptans, more often than men ( Brusa et al, 2015 ). Additionally, it has been suggested that women are more susceptible to secondary headache production in both traumatic brain injury and ischemic stroke compared to males ( Tentschert et al, 2005 ; Lucas et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we excluded articles investigating the effects of migraine therapies and treatments to focus on sex-and gender-differences in migraine as a disease, itself, rather than sex-specific differences related to individual treatment strategies, adherence, and migraine management. We acknowledge there are important (behavioral) differences between males and females with respect to treatment, but these are outside the scope of the present review (102,120). Robbins and Bernat did not identify articles on treatment efficacy stratified by sex, illustrating that this topic also needs more attention in the field of migraine treatment research (121).…”
Section: Strengths and Limitationsmentioning
confidence: 91%
“…These gaps are often created simply by patients choosing not to seek medical intervention, leading to suboptimal care. Gaps have been noted for allergic rhinitis, 48 migraine headaches, 49 allergic conjunctivitis, 50 , 51 acne, 52 and overactive bladder. 53 More allergy sufferers, for example, should be using topical intranasal steroids than the number that currently do.…”
Section: Pharmacist Prescribingmentioning
confidence: 99%